Co-doping of tellurium with bismuth enhances stability and photoluminescence quantum yield of Cs2AgInCl6 double perovskite nanocrystals. Issue 42 (20th October 2022) - Wang, Shixun; Shi, Ran; Tang, Bing; Xiong, Yuan; Portniagin, Arsenii; Zhao, Xin; Kershaw, Stephen V.; Long, Run; Rogach, Andrey L.
Abstract : The Bi 3+ and Te 4+ co-doping strategy and in situ growth regulation via external oxygen vacancies were applied to Cs2 AgInCl6 nanocrystals, resulting in a high photoluminescence quantum yield of 34%, as a consequence of restrained Ag/In vacancies. Abstract : The co-doping of double perovskites is a useful approach in terms of improving their stability and photoluminescence quantum yield. Herein, Bi 3+ and Te 4+ cations have been co-doped into Cs2 AgInCl6 nanocrystals. Doping with Te 4+ cations promotes radiative recombination of self-trapped excitons due to increased defect formation energies of silver and indium vacancies, according to experimental and theoretical results. When used in excess, the TeO2 precursor would generate residual TeO2, Te2 O3 Cl2, R2 TeO, or all three of them, which confined undesired chlorine ions on oxygen vacancies to counteract the pull from the Cs2 AgInCl6 host, resulting in improved coordination with surface oleic acid ligands. As a result, 1% Bi and 8% Te co-doped Cs2 AgInCl6 nanocrystals reach a high photoluminescence quantum yield of 34% and show an improved stability, maintaining over 70% of their original emission intensity after storage for more than 1 month. These findings are important in the context of producing high-performance properly doped double perovskite nanocrystals for optoelectronic applications.